Pedagogical terms of realization of program development professionally of important qualities of students of economic specialities by tools of football - Maliar E.I; Lebid M.R (Kharkov National Pedagogical University, 2010)
The article is devoted to the questions of professionally oriented psychophysical preparation of students of higher educational establishments of economic type. In the article the pedagogical terms of effective realization of the program of development professionally of important qualities of future economists are given by the tools of football: rational distributing of educational material during 4th semesters; personality-oriented character of study of students; rational distributing of time on general and special physical preparation; differentiated planning of parameters of the physical loading; complex control of dynamics of physical health, tech-tactical and physical preparedness of students.